Digital Marketing Capability Across Industries: A Narrative Literature Review and Conceptual Synthesis of Six Core Dimensions - Zefanya Andryan Girsang; Muhammad Mujahid Dakwah; Dinis Cahyaningrum; Zamroni Alpian Muhtarom (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2026)
Digital Marketing Capability (DMC) has become an important strategic capability that enables organizations to leverage digital technologies to improve marketing performance and sustain competitive advantage. However, existing research remains fragmented due to inconsistent definitions, diverse measurement approaches, and varying industrial contexts. This study aims to synthesize the conceptual development of DMC, examine its operationalization, identify its core dimensions across industries, and propose future research directions. A narrative literature review was conducted by analyzing 13 peer-reviewed journal articles covering multiple industrial contexts, including small and medium-sized enterprises (SMEs), agriculture, hospitality and tourism, manufacturing, and industrial firms. Using thematic synthesis, the review compares conceptualizations, measurement approaches, and industrial applications of DMC. The findings show that DMC has evolved from a technology adoption perspective into a strategic organizational capability integrating digital technologies, customer engagement, platform management, data analytics, and stakeholder collaboration. The study proposes six core dimensions of DMC: Digital Market Sensing Capability, Digital Content and Communication Capability, Digital Customer Engagement Capability, Digital Platform Management Capability, Digital Data Analytics Capability, and Digital Business Stakeholder Engagement Capability. These findings provide an integrated conceptual framework that supports future empirical research and the development of standardized DMC measurement instruments across diverse industrial contexts.